THE EFFECT OF SUBJECTIVE WELL-BEING ON LEARNING INDEPENDENCE WITH LEARNING MOTIVATION AS A MEDIATOR - Tri Putri Handayani; Nefi Darmayanti; Yudistira Fauzi Indrawan (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Education is a process in which there are rules and procedures that every student must have. Improving the quality of education requires student learning independence in the learning process. Participants in this research were all students of the Dharma Patra Pangkalan Berandan Private High School in Sei Lepan sub- district, Langkat district, totaling 497 students. The quantitative method approach used in this research is an explanatory or explanatory quantitative approach. Based on the research results which show a CR value of 2,647 > 1.96 and a P value of < 0.05, it can be concluded that there is a significant influence between subjective well-being and learning motivation. In other words, students who have a higher level of subjective well-being tend to have stronger learning motivation. The relationship between subjective well-being and learning motivation is complex and influenced by various factors. However, the results of this study emphasize the importance of paying attention to students' emotional well-being and life satisfaction as an integral part of strategies to increase student motivation and learning outcomes.